Meta-analysis of effect of routine enteral nutrition on postoperative outcomes after pancreatoduodenectomy - Tanaka, Motomu; Heckler, Max; Mihaljevic, André Leopold; Probst, Pascal; Klaiber, Ulla; Heger, Ulrike; Hackert, Thilo (The British journal of surgery, 2019)
Background The optimal nutritional treatment after pancreatoduodenectomy is still unclear. The aim of this meta-analysis was to investigate the impact of routine enteral nutrition following pancreatoduodenectomy on postoperative outcomes. Methods RCTs comparing enteral nutrition (regular oral intake with routine tube feeding) with non-enteral nutrition (regular oral intake with or without parenteral nutrition) after pancreatoduodenectomy were sought systematically in the MEDLINE, Cochrane Library and Web of Science databases. Postoperative data were extracted. Random-effects meta-analyses were performed to compare postoperative outcomes in the two arms, and pooled odds ratios (ORs) or mean differences (MDs) were calculated with 95 per cent confidence intervals. In subgroup analyses, the routes of nutrition were assessed. Percutaneous tube feeding and nasojejunal tube feeding were each compared with parenteral nutrition. Results Eight RCTs with a total of 955 patients were included. Enteral nutrition was associated with a lower incidence of infectious complications (OR 0·66, 95 per cent c.i. 0·43 to 0·99; P = 0·046) and a shorter length of hospital stay (MD -2·89 (95 per cent c.i. -4·99 to -0·80) days; P < 0·001) than non-enteral nutrition. Percutaneous tube feeding had a lower incidence of infectious complications (OR 0·47, 0·25 to 0·87; P = 0·017) and a shorter hospital stay (MD -1·56 (-2·13 to -0·98) days; P < 0·001) than parenteral nutrition (3 RCTs), whereas nasojejunal tube feeding was not associated with better postoperative outcomes (2 RCTs). Conclusion As a supplement to regular oral diet, routine enteral nutrition, especially via a percutaneous enteral tube, may improve postoperative outcomes after pancreatoduodenectomy.